An efficient extraction of lead metal from waste cathode ray tubes (CRTs) through mechano-thermal process by using carbon as a reducing agent. (1st April 2017) - Singh, Narendra; Li, Jinhui
Abstract: An efficient mechano-thermal method was developed for lead removal from the CRTs funnel glass. The method comprises the activation of funnel glass with carbon by the planetary ball-milling apparatus. The mixture has been sintered for different lengths of time. The separation phenomenon was accelerated by the thermal treatment in the presence of carbon, the lead oxide (PbO) in a funnel glass quickly reduced into Pb and assembled on the surface of the glass matrix. With acid leaching, lead was efficiently removed from the treated glass residues. The optimum temperature, carbon powder adding amount, and holding time were 900 °C, 10%, and 30 min, respectively. During the process, more than 99 wt% of lead can be volatilized from the funnel glass and 93.60 wt% of lead was removed by the leaching process. The findings in this study provides an efficient and practical application for CRTs funnel glass detoxification and reutilization. Graphical abstract: